Kesesuaian Citra Diri Dan Kesukaan Merek Pada Konsumen - Cahyani, Rusnandari Retno (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2013)
This  research  prove  an  effect  according  to  image  to  consumer  fasting  and  customer satisfaction product for goal to influence between self-image congruency with a brand, and brand preference. This study to knowing relationship between self-image congruency with a brand and satisfaction with the brand.Keyword: Self-image congruency, Satisfaction, Brand preference.